Development of traceability model for inexpensive high-volume items - Khabbazi, Mahmood Reza (2009)
Having a traceability system in a company which produces goods or services is something that can help to assure the customer’s or the company’s security, safety,and satisfaction. Information created by this system will help to improve the quality and also to find the clues of the production problem occurrences. A database system in which storage and retrieval of information is performed is the most applicable method to meet this need and fulfill this demand. This thesis focuses on the data modeling for traceability system in information layer of manufacturing control system that is devoted for non-expensive high volume items as final goods in all aspects production and control operations. A useful database system that could be applicable in many identical cases for lot-base traceability for material flow is developed through data modeling. The designed model improves the applicability of lot traceability with dynamic store and retrieval of the manufacturing and quality data. The functionality of the computerized traceability information system requirement is successfully evaluated through implementing data queries. As the result, the developed model promises to handle fundamental issues of traceability system effectively. It supports for customization and real-time control of material flow in all quality and production operation processes. Through prototype implementation of the model, recording deviations and therefore, assessing their impacts become easier. The computerized information system with better visibility and dynamic data processing handles all traceability usages and applications efficiently. Due to the case and nature of this thesis is not for a complex enterprise, it can be concluded that the model is initially applicable to environment with identical operational boundaries and complexity. A case study in car component industry which provides the fundamental idea and key solution is presented. ERM (Entity Relationship Modeling) and pertaining diagrams (Entity Relationship Diagram) are used as modeling tool for its easy-understanding and applicability in modeling of high volume data. Microsoft Access is selected as database platform in this study due to its availability at all manufacturers especially small-to-medium size enterprises. The designed database includes main console with two options of data entry forms, and reports. Data entry is made manually and from customer order to final product inspections. Report option is designed to acquire desired traceability information such as lot relations. The solution is limited to material flow control excluding all resources and capacity related issues in the planning functionality. The model developed for a single company environment with batch production system for Make-to-Order.